The Paussus (Scaphipaussus) lanxangensis species group of Indomalayan ant nest beetles (Coleoptera, Carabidae, Paussinae, Paussini) with description of a new species - Nagel, Peter (Zootaxa, 2024)
The new species Paussus agatae sp. nov. could not easily be allocated to an established subgenus or even species group. The informal Paussus lanxangensis species group is established to include the new species and other related species. Its diagnostic characters are described and screened for possible use in cladistic analyses in the future. Currently, it consists of five described species of the Indomalayan mainland, which are arranged in a key.